Cutting back mosaic virus - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Current Pandemic of Cassava Mosaic Virus Disease in East Africa and its Control. G W Otim-Nape et al. Co-published by Uganda National Agricultural Research Organisation, the British Department for International Development and the Natural Resource